Irmãs em Sião: uma análise discursiva dos grupos feministas na Igreja de Jesus Cristo dos Santos dos Últimos Dias e seus circuitos de comunicação e consumo - Massimini, Adille Rigoni (2022)
This dissertation aims to analyze the discursive constitution of feminist resistance spaces in the Church of Jesus Christ of Latter-day Saints and how it relates to the symbolic consumption of religion. Thus, we chose as a research question: what are the communication spaces used by feminist resistance in the Church of Jesus Christ of Latter-day Saints and what are the main discourses mediated in these spaces? For this, our empirical object is the posts of the Feminist Mormon Housewives Society's discussion group on Facebook and, as a theoretical object, the discourses that structure these productions. The research starts from the studies of gender and subjection proposed by Judith Butler and dissent through the lens of Jacques Rancière, also counting on authors who already discuss these issues concerning the Church of Jesus Christ of Latter-day Saints, such as Taylor G. Petrey, and of Mormon feminist studies, through authors such as Claudia Bushman, Joanna Brooks, Rachel Hunt Steenblik, and Hannah Wheelwright. We seek to debate the creation of new spaces so that feminist discourse could exist among Church members, thinking about the existing power relations within the institution and, mainly, who has access to speech within the Church. Due to its strong focus on social problems and power relations, critical discourse analysis, proposed by Teun A. van Dijk, will be our great ally in methodological terms to investigate the communicational spaces used by Mormon feminism. It will allow us to think about how the feminist Mormon identity requires a transit between the consumption circuits linked to religion and feminist discourses.